Case report: CAR-T cell therapy-induced cardiac tamponade - Sarfati, Sacha; Norbert, Misa Eugène; Hérault, Antoine; Giry, Marion; Makké, Jade; Grall, Maximilien; Savouré, Arnaud; Camus, Vincent; Alani, Mustafa; Tamion, Fabienne; Latouche, Jean-Baptiste; Girault, Christophe (Frontiers in Cardiovascular Medicine, 2023)
CD19-specific chimeric antigen receptor T (CAR-T) cell therapy has recently been found to improve the prognosis of refractory diffuse large B-cell lymphoma (DLBCL). However, CAR-T cells induce numerous adverse events, especially cytokine release syndrome (CRS) that is frequently associated with cardiovascular manifestations. Among the latter, acute pericardial effusion represents less than 1% of cases and cardiac tamponade has only been reported once. The management and outcome of this severe complication are not well established. We report here, a case of cardiac tamponade associated with CRS in a context of CAR-T cell therapy, which required urgent pericardiocentesis. Case summary: A 65-year-old man with refractory DLBCL was treated with CAR-T cell therapy. He had a history of dilated cardiomyopathy with preserved ejection fraction and transient atrial fibrillation. He exhibited a pericardial localization of the lymphoma on the second relapse. One day after CAR-T cell infusion the patient was diagnosed with grade 1 CRS. Due to hypotension, he was treated with tocilizumab and dexamethasone, and then transferred to intensive care unit (ICU). Echocardiography performed at ICU admission showed acute pericardial effusion with signs of right ventricular heart failure due to cardiac tamponade. It was decided to perform pericardiocentesis despite grade IV thrombocytopenia in a context of aplasia. Analysis of pericardial fluid showed an important population of lymphoma cells and 73% of CAR-T cells amongst lymphocytes, a level that was similar in blood. Hemodynamic status dramatically improved after pericardiocentesis, and no recurrence of pericardial effusion occurred. The patient was discharged from ICU after two days and initially exhibited a good response to DLBCL treatment. Unfortunately, he died fifty days after CAR-T cell therapy initiation due to a new DLBCL relapse. Conclusion: Patients with a pericardial localization of DLBCL should be considered at high risk of cardiac tamponade if undergoing CAR-T cell therapy and presenting CRS. In this case, cardiac tamponade seems directly related to CAR-T cell expansion. Pericardiocentesis should be considered as a feasible and effective treatment if the risk of bleeding is well controlled, in association with anti-IL6 and corticosteroids.